ANALISIS DATA PENJUALAN DAN POLA PEMBELIAN MELALUI SISTEM INFORMASI BERBASIS WEB UNTUK STRATEGI PEMASARAN (STUDI KASUS UMKM KABUPATEN SERANG) - Toni Fathoni; Khabi Bunajjar; Nastiti Tri Permatasari (Jurnal Komunikasi, 2025)
This study aims to analyze the implementation of web-based information systems in Micro, Small, and Medium Enterprises (MSMEs) in Serang Regency as part of digital transformation efforts in the local business sector. The research employs a descriptive qualitative approach through observations and interviews with MSME owners who have adopted web-based systems in their operations. The findings show that the implementation improves operational efficiency, enhances transaction accuracy, and simplifies stock management and financial reporting. Moreover, web-based information systems enable entrepreneurs to analyze sales data for formulating data-driven marketing strategies. However, several challenges were identified, including limited digital literacy, a shortage of skilled personnel, and data security issues. Therefore, government and educational institutions need to provide continuous training and technical support. Overall, the implementation of web-based information systems contributes to improving competitiveness, marketing effectiveness, and accelerating digital transformation among MSMEs in Serang Regency